Sejarah Islam Di Vietnam Sebagai Pembelajaran Sejarah Di SMA Kelas XII - Dian Saputri, Restu (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2024)
The Cham people, the majority of whom adhere to Hinduism, have dominated the central and southern regions of Vietnam for centuries. Vietnam became one of the first countries in Asia to interact with Islam over time. Improvements in the lives of Muslims in Vietnam have occurred since the socialist government implemented the Doi Moi (Renovation) policy in 1986, allowing native Muslim communities to perform congregational prayers. Although the majority of Vietnam's population follows Buddhism, Islam in the country is a minority religion. Factors such as religion, socialism, and remote geographical location have influenced the Muslim minority in Vietnam. This sets Vietnam apart from other Southeast Asian countries with more accessible geographical locations for Muslim traders or merchants. The research problem is summarized as follows: 1. To determine when Islam entered Vietnam. 2. To identify the Islamic schools of thought followed by Muslims in Vietnam. 3. To understand the current status of Islam in Vietnam. Qualitative research methods are applied in this study, and qualitative analysis findings indicate that the history of Islam in Vietnam is predominantly associated with the Cham ethnic group. It is estimated that Islam entered the territory of the Champa kingdom during the Zong dynasty in Champa during the period from 960-1280 CE. Thus, the spread of Islam has had a significant impact both domestically and internationally, widely influencing society to this day.